Car Parking Distance Controller Using Ultrasonic Sensors Based On Arduino Uno - Susilo, Jenli; Febriani, Anita; Rahmalisa, Uci; Irawan, Yuda (Universitas Muhammadiyah Yogyakarta, 2021)
The design of a car parking sensor is done because there are some problems such as the absence of parking attendants from 18:00 to 06:00 and the lack of parking attendants so the researchers took the title of arduino uno-based car parking distance controller by using ultrasonic sensors in this study using 3 main components, namely Arduino UNO, Arduino MP3 Shield and Ultrasonic HC-SR04. Arduino Shield MP3 is a module that is used to play sound. MP3 which can give voice commands that have been programmed before using Arduino IDE and combined with Ultrasonic HC-SR04 components in the calculation of the distance to the object. The distance (cm) obtained as input is then processed and then combined with the Arduino Shield MP3, then at a predetermined distance will output a predetermined voice command. Then the method used is the prototype method which starts from designing, writing the system, implementing it with the aim of making a prototype of a car parking sensor and testing it with a prototype. Conclusion testing the car sensor sensor car makes it easy for car drivers to park the car.